Antitumour activity of 2-dihydroailanthone from the bark of Ailanthus altissima against U251. (1st September 2016) - Wang, Ruxing; Xu, Qian; Liu, Lei; Liang, Xiujun; Cheng, Luyang; Zhang, Manli; Shi, Qingwen
Abstract: Context The bark of Ailanthus altissima (Mill.) Swingle (Simaroubaceae) is traditionally used to treat ascariasis, diarrhoea, spermatorrhoea, bleeding and gastrointestinal diseases. Objective The objective of this study is to investigate the antitumour activity and mechanism of 2-dihydroailanthone isolated from A. altissima. Materials and methods The U251 cells were treated with 1.00, 4.00 and 8.00 μg/mL of 2-dihydroailanthone for 48 h and the normal cells treated with 20.00 μg/mL of 2-dihydroailanthone were tested as well. Proliferation inhibition of 2-dihydroailanthone on the cells was tested by MTT. Apoptosis and cell-cycle distribution in U251 cells with 1.00, 3.00 and 5.80 μg/mL of 2-dihydroailanthone for 48 h were determined by flow cytometry, respectively. The expression of the apoptosis-related genes and proteins was analysed by RT-PCR and Western blot method, respectively. Results MTT assay revealed that 2-dihydroailanthone inhibited U251 cells proliferation. The cell viability of U251 cells was 62.82, 31.34 and 25.58%, and that of three normal cells was 72.75, 82.74 and 44.92%, respectively. Flow cytometry assay showed that 2-dihydroailanthone induced apoptosis and G0/G1 phase cycle arrest towards U251 cells. The late apoptotic cells were 11.37, 21.73 and 33.83%, and the cells cycle distributed in the G0/G1 accounted for 48.85, 62.77 and 64.40%, respectively. The Western blot and RT-PCR assay showed that up-regulation of pro-apoptotic bax protein and down-regulation of anti-apoptotic bcl-2 protein as well as their mRNA on U251 cells might be related to the apoptosis induction and proliferation inhibition. Conclusion An important bioactive component, 2-dihydroailanthone, has antitumour effects, enlightening a novel source of phytomedicines in tumour therapy.